Personality and symptom severity in Obsessive–Compulsive Disorder: The mediating role of depression - Rees, Clare; Roberts, Lynne; van Oppen, P.; Eikelenboom, M.; Hendriks, A.; van Balkom, A.; van Megen, H. (Elsevier Sciences Ltd, 2014)
Elevated levels of Neuroticism and lower levels of Extraversion have been reliably shown in patients with anxiety and depressive disorders and some studies have demonstrated these patterns amongst patients diagnosed with Obsessive–Compulsive Disorder (OCD). However, because comorbid anxiety and depression is common in OCD, it is unclear whether the previously observed relationships are due to comorbid anxiety and depression or are more specifically related to the presence of OCD. This study sought to disentangle the relationship between personality and OCD by investigating the relationship between Extraversion, Neuroticism and OCD symptom severity and illness duration. Additionally, we explored the relationship between these variables and the additional variable of depression. Specifically, we tested whether depression mediated these relationships amongst a sample of 322 outpatients diagnosed with OCD. We found that depression fully mediated the relationship between personality and OCD symptom severity but not duration. Indeed, neither personality nor depression could explain illness duration. The results suggest that depression is an important variable to consider when understanding OCD symptom severity and trumps personality variables in terms of its explanatory power. The results also suggest that further work is needed to identify the variables that best explain illness duration in OCD.